β-diversidade das comunidades de oligoquetas da área de endemismo de Belém. - García, Luis Manuel Hernández (2019)
The Belém Endemism Area (BEA) is actually the most deforested area from the Amazon, there are a mosaic of land use with different levels of degradation that allow to study complex ecological interactions and also has an important quantity of unknown edaphic niches. Earthworms represent one of the most important groups of soil fauna, but they are succeptible to changes in land-use, especially native earthworms which can also be extint over long time disturbance effect, and when the affected area has large dimension i.e landscape level. In this work we studied the earthworm communities in different conditions of land-use, landscape and relief, located in the Gurupi Biological Reserve and neighboring settlements of the Centro Novo do Maranhão, Itinga do Maranhão, and Bom Jesus do Maranhão counties. Others samples collected in 2010-2015 in Tome Açú, São Luís, São José do Ribamar, and Alcântara counties were used to complete the new species taxonomic descriptions of the BEA. Earthworms were collected in the raining season (2015-2017) using the modified TSBF method (3 monolith, 20cm in deepth) complemented whit an active search over 4h/research on those microhabitats supceptivel to had earthworm. As results, we found 8 new species to science, two of that belonged in two new genera. Another species, also potentially new to science, are over description. Some of the native species can survive after deforestation events, however the relation between earthworm communities and land-use depend on the landscape type. Despite there is not has local changes of earthworm diversity, we estimate a high turnover (17-18%) of species by land-use type. The β-diversity model showed there are different factors influencing the earthworm turnover, and the geographical distance is only important at the final stage of succession. The loss of native earthworms after deforestation events was minimal because of survival, of species habiting the ancient forest, in pastures. Therefore, the biodiversity recuperation is fast, but the composition changes depends on the landscape type and the history back of landsuse type.